PROBLEMATIKA PEMBELAJARAN TAHFIDZ AL-QURAN PADA MASA PANDEMI COVID-19 DI SMP ISLAM TERPADU INSAN PERMATA MALANG - Lamya Zulfiana; Dzulfikar Rodafi; Dian Mohammad Hakim (VICRATINA, 2022)
The COVID-19 virus pandemic has affected all aspects of life, ranging from economic, social, and educational. This requires that in the world of education it changes to distance learning. At SMPIT Insan Permata Malang decided to carry out all learning activities online. Therefore, in learning Tahfidz Al-Quran, the teacher who teaches Tahfidz must have strategies that are used in learning. The focus of the research discusses the strategies used by teachers who teach Tahfidz Al-Quran, the implementation of methods, and problems and solutions in learning Tahfidz Al-Quran during the Covid-19 pandemic. The research is carried out with a qualitative type of research. The results of the study that the learning strategies used by teachers in learning Tahfidz Al-Quran are: 1) Learning through the LMS application, 2) Classical strategies read, 3) Memorization guide videos, 4) Using one mushaf. Implementation of the method: 1) Sending memorized videos, 2) Reading rhythms using bayati 3) Depositing rote memorization. Problems and solutions: 1) Lack of parental support, with the solution the teacher creates a group with parents to control students in learning. 2) Network Constraints, with learning solutions moving to whatsapp group. 3) Not meeting the memorization target, with the solution of the teacher increasing competence to encourage students to be more enthusiastic about memorizing the Quran. 4) Student background, with the teacher's solution gives birth to a method that can affect every difference in student background.